A method for preparing a gallium and zirconium co-doped zinc oxide target

Through the preparation method of gallium and zirconium co-doped zinc oxide targets, the existing aluminum-doped zinc oxide thin films have been solved, and the zinc oxide doped conductive film with low resistivity and high mobility is realized, which improves the efficiency of thin-film solar cells.

CN119241226BActive Publication Date: 2025-04-25LUOYANG JINGLIAN OPTOELECTRONIC MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411793754.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-25
Estimated Expiration
2044-12-09

Smart Images

  • Figure CN119241226B_ABST
    Figure CN119241226B_ABST
Patent Text Reader

Abstract

The present application discloses a preparation method of a gallium and zirconium co-doped zinc oxide target, which relates to the technical field of target materials. The preparation method comprises the following steps: S1: uniformly mix zirconium oxide, gallium oxide, water and a dispersant, grind to obtain slurry 1; S2: uniformly mix zinc oxide, water and a dispersant, add slurry 1, mix uniformly, then add a binder and a plasticizer, mix uniformly, grind to obtain slurry 2; S3: spray-dry and granulate slurry 2, sieve to obtain granular powder; S4: hydraulically and cold isostatically press the granular powder to obtain a blank; S5: sinter the blank, and after cooling, obtain a gallium-zirconium co-doped zinc oxide target. The gallium and zirconium co-doped zinc oxide target prepared by the present application has a higher relative density and a lower resistivity; after magnetron sputtering, the obtained film has better electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of target materials, and in particular to a method for preparing a gallium and zirconium co-doped zinc oxide target material. Background Art

[0002] Transparent conductive oxide (TCO) films are a type of material with high visible light transmittance and low resistivity. They are widely used in various optoelectronic devices, including flat panel displays, touch screens, light-emitting diodes, solar cells and other optoelectronic devices. With the increasing development of electronic products and optoelectronic devices, traditional conductive oxides such as indium tin oxide (ITO) have large price fluctuations and supply risks due to the scarcity and high prices of elements such as indium and tin. Therefore, finding alternative materials has become an important issue. Zinc oxide sputtering targets have emerged. They have the advantages of low price, abundant resources, and simple preparation process, which can effectively solve the problems of scarce indium and tin resources and high prices.

[0003] At present, the preparation technology of zinc oxide sputtering targets has gradually matured, including chemical vapor deposition, physical vapor deposition, magnetron sputtering and other methods. By optimizing the preparation process and process parameters, zinc oxide films with high transparency, low resistivity, good crystallinity and density can be obtained, which can meet the needs of different application fields.

[0004] Since zinc oxide thin films have the characteristics of wide bandgap, safety, non-toxicity and easy doping, doped zinc oxide thin films can also be used in thin-film solar cells. The main doping methods for ZnO system materials include boron doping (BZO), aluminum doping (AZO), gallium doping (GZO), and magnesium gallium co-doping (MGZO). Among them, AZO and GZO thin films have excellent optical and electrical properties and have attracted much attention. They can be used in thin-film solar cells, but when these two films work at higher temperatures, the resistivity increases rapidly, exposing the problem of insufficient thermal stability.

[0005] Xiao Bin (Preparation and Properties of AZO Transparent Conductive Films, Master's Thesis of South China University of Technology, 2015) studied the room temperature preparation and properties of Al-doped ZnO thin films by DC magnetron sputtering, and studied the effect of target Al content on the structure, optical and electrical properties of AZO thin films.

[0006] However, the aluminum-doped zinc oxide transparent conductive film has low mobility and high resistivity, and has limited effect on improving the efficiency of thin-film solar cells. Summary of the invention

[0007] In order to obtain a zinc oxide-doped conductive film with low resistivity and high mobility, the present application provides a method for preparing a gallium and zirconium co-doped zinc oxide target.

[0008] The present application provides a method for preparing a gallium and zirconium co-doped zinc oxide target material, which adopts the following technical solution:

[0009] A method for preparing a gallium and zirconium co-doped zinc oxide target comprises the following steps:

[0010] S1: mixing zirconium oxide, gallium oxide, water and a dispersant uniformly, grinding and obtaining slurry 1;

[0011] S2: After zinc oxide, water and dispersant are mixed evenly, slurry 1 is added, mixed evenly, and then a binder and a plasticizer are added, mixed evenly, and ground to obtain slurry 2;

[0012] S3: spray-drying and granulating the slurry 2, and sieving to obtain granular powder;

[0013] S4: hydraulically and cold isostatically press the granular powder to obtain a green embryo;

[0014] S5: Sintering the green embryo, and obtaining a gallium-zirconium co-doped zinc oxide target after cooling.

[0015] By adopting the above technical solution, the ionic radius of zirconium and gallium is close to that of zinc, and the zirconium ion (Zr 4+ ) and gallium ions (Ga 3+ ) replaces zinc ions (Zn 2+ ) can provide more electrons and more oxygen holes, thereby improving the conductivity and mobility of the film. In addition, the zinc oxide target co-doped with zirconium and gallium has a low sintering temperature, which can reduce damage to the equipment.

[0016] The addition of dispersants, on the one hand, can make the metal oxide particles carry the same charge on their surface after adsorption on the metal oxide surface, so that the metal oxide particles can be evenly dispersed in the system. On the other hand, the anchoring groups in the dispersants can be firmly adsorbed on the surface of zinc oxide particles, while the solvated segments stretch in the medium to form a structure similar to a "protective shell". When metal oxide particles approach each other, the solvated segments will repel each other, preventing the aggregation of particles and maintaining a dispersed state. This steric hindrance effect can effectively prevent the agglomeration of particles.

[0017] The addition of plasticizer can play the role of steric hindrance and weaken the interaction between particles, making the particles easier to disperse. At the same time, the binder also begins to adsorb on the surface of the particles at this stage, using the good dispersion conditions created by the plasticizer to better cover the surface of the particles, chemically react or physically adsorb with the active sites on the particles to form a bond. The combined effect of the two can effectively improve the plasticity and bonding strength of the target material.

[0018] The slurry 2 is spray dried and sieved to obtain a finer and more uniform granular powder, which makes the distribution of metal oxide particles more uniform and avoids the segregation of components. This uniformity of particles has better filling properties during the molding process. Because the particles are uniform in size and reasonably distributed, they can be more closely packed together when subjected to pressure in the mold, forming a green embryo with higher density and more uniform structure.

[0019] Among them, hydraulic pressing followed by cold isostatic pressing of granular powder can better maintain the shape stability of the target material, reduce the pores and voids inside the blank, and make the final density and strength of the target material higher. The high-density target material can better withstand processes such as sputtering during use, reduce the loss and deformation of the target material, and the high-strength target material can withstand external forces during subsequent processing, transportation and use, reducing the risk of target material breakage or damage.

[0020] During the sintering process, the uniformity of the particles can better fuse with each other, which can more effectively change the lattice structure of zinc oxide and increase its carrier concentration, so that the target material can show better performance in application.

[0021] Preferably, in step S1, zirconium oxide accounts for 0.2% to 3% of the total mass of the metal oxide, gallium oxide accounts for 0.5% to 5% of the total mass of the metal oxide, the dispersant accounts for 0.5% to 0.8% of the total mass of the metal oxide, and water accounts for 15% to 50% of the total mass of the metal oxide.

[0022] Preferably, in step S1, zirconium oxide, gallium oxide and water are mixed for 30 min to 180 min, and then a dispersant is added and mixed for 30 min to 180 min, and then transferred to a sand mill, the speed of the sand mill is set to 600 to 1000 rpm, and ground for 200 to 300 min to obtain a slurry with a particle size D90<0.7 μm.

[0023] Preferably, in step S2, zinc oxide accounts for 92% to 99.3% of the total mass of the metal oxide, water accounts for 30% to 100% of the total mass of the metal oxide, the dispersant accounts for 0.5% to 1.5% of the total mass of the metal oxide, the binder accounts for 1% to 5% of the total mass of the metal oxide, and the plasticizer accounts for 0.25% to 1.25% of the total mass of the metal oxide.

[0024] Preferably, in step S2, zinc oxide, water and dispersant are mixed for 30 min to 180 min, then slurry 1 is added and mixed for 30 min to 180 min, then a binder and a plasticizer are added and mixed for 30 min to 180 min, and then transferred to a sand mill, the speed of the sand mill is set to 600 to 2000 rpm, and grinding is performed for 30 to 300 min to obtain slurry 2 with a particle size D90<0.7 μm.

[0025] Preferably, the dispersant is at least one of sodium hexadecyl sulfonate, carboxylates, and sodium hexametaphosphate.

[0026] Preferably, the carboxylate is sodium polyacrylate.

[0027] Preferably, the dispersant includes sodium hexadecyl sulfonate and sodium hexametaphosphate, and the mass ratio of the sodium hexadecyl sulfonate to the sodium hexametaphosphate is 0.3-0.7:1.

[0028] By adopting the above technical solution, sodium hexadecyl sulfonate and sodium hexametaphosphate can play a synergistic dispersing effect when used in combination. This is because: on the one hand, sodium hexadecyl sulfonate and sodium hexametaphosphate will both ionize negative charges in aqueous solution, and the negative charges carried by the two will be superimposed on each other, further enhancing the negative charge on the surface of the metal oxide particles, thereby increasing the electrostatic repulsion between the particles to a greater extent, so that the zinc oxide particles can be more stably dispersed in the system. On the other hand, the long-chain alkyl of sodium hexadecyl sulfonate provides a more flexible steric hindrance, while the cross-linked structure of sodium hexametaphosphate provides a more stable steric hindrance. The two work together to make the dispersion state of zinc oxide particles in the solution more stable.

[0029] Preferably, the dispersant comprises sodium hexadecyl sulfonate and sodium polyacrylate, and the mass ratio of the sodium hexadecyl sulfonate to the sodium polyacrylate is 1:1-3.

[0030] By adopting the above technical solution, sodium hexadecyl sulfonate and sodium polyacrylate can play a synergistic dispersing effect when used in combination. This is because: on the one hand, sodium hexadecyl sulfonate is mainly dispersed by electrostatic repulsion and steric hindrance effect, but its molecular structure is relatively small. When used alone, the dispersion effect may be affected to a certain extent, and the high molecular structure of sodium polyacrylate makes the dispersed state have better stability and anti-interference ability. On the other hand, sodium hexadecyl sulfonate can preferentially find suitable adsorption sites on the surface of metal oxide particles and adsorb quickly, which also provides more binding sites for the adsorption of sodium polyacrylate, so that sodium polyacrylate can be more firmly adsorbed on the surface of the particles, further enhancing the negative charge density and steric hindrance effect of the particles, thereby further improving the dispersing ability of the dispersant on the metal oxide particles.

[0031] Preferably, the binder is at least one of polyacrylic acid, polyvinyl alcohol and hydroxypropyl methylcellulose.

[0032] Preferably, the binder comprises polyvinyl alcohol and hydroxypropyl methylcellulose, and the mass ratio of the polyvinyl alcohol to the hydroxypropyl methylcellulose is 1.2-1.4:1.

[0033] By adopting the above technical solution, polyvinyl alcohol and hydroxypropyl methylcellulose are compounded and used to play a good synergistic bonding role. Using a slightly higher proportion of polyvinyl alcohol helps to provide a stronger bonding backbone. The abundant hydroxyl groups on the polyvinyl alcohol molecular chain can form hydrogen bonds with the active groups on the surface of zinc oxide particles and slurry particles. More polyvinyl alcohol can better wrap the particles and build a preliminary bonding framework between the particles. The flexibility and special spatial conformation of the hydroxypropyl methylcellulose molecular chain enable it to penetrate into the microscopic areas that polyvinyl alcohol cannot completely cover, making the contact between the particles closer, which can improve the mobility of carriers, reduce resistivity, and thus improve the conductivity.

[0034] Preferably, the binder comprises polyacrylic acid and polyvinyl alcohol, and the mass ratio of the polyacrylic acid to the polyvinyl alcohol is 0.5-0.7:1.

[0035] By adopting the above technical scheme, polyacrylic acid and polyvinyl alcohol are compounded and used, which can play a good synergistic bonding effect. On the one hand, polyvinyl alcohol molecular chain contains a large number of hydroxyl groups, and polyacrylic acid molecular chain contains carboxyl groups. The carboxyl groups will be partially ionized to form carboxylate ions. The unionized carboxyl groups can form hydrogen bonds with the hydroxyl groups on polyvinyl alcohol. This hydrogen bonding plays a bridge role between the two polymers, connecting them closely together, enhancing the cohesive force of the bonding system, making the zinc oxide particles and the slurry particles better combined together, thereby improving the overall bonding strength. And the carboxylate ions can chemically adsorb or weakly react with the positively charged part of the particle surface or other substances with opposite charges to a certain extent. The formation of these chemical bonds is more solid than simple physical adsorption, which can greatly enhance the bonding force between the zinc oxide particles and the slurry particles. On the other hand, the polyvinyl alcohol molecular chain is relatively regular, and can occupy a certain space in the bonding process to form a more ordered structure, while the polyacrylic acid molecular chain has certain stretchability and flexibility due to the presence and partial ionization of carboxyl groups, and can better adapt to the irregular shape and microstructure of the particle surface. The complementarity of the two in spatial structure enables them to jointly fill the gaps between the particles, forming a tighter bonding layer, improving the sealing and stability of the bond, and maintaining this good bonding state during subsequent processing (such as drying, sintering, etc.), thereby increasing the mobility of carriers, reducing resistivity, and thus improving conductivity.

[0036] Preferably, the plasticizer is at least one of polyethylene glycol, polyhydroxyethyl acrylate, and ethers.

[0037] Preferably, the ethers are polyethylene glycol ethers.

[0038] Preferably, the binder is mixed with water to form a uniform dispersion, which is then added to the zinc oxide system.

[0039] Preferably, the plasticizer is mixed with water to form a uniform dispersion, which is then added to the zinc oxide system.

[0040] Preferably, the plasticizer comprises polyethylene glycol and polyethylene glycol ether, and the mass ratio of the polyethylene glycol to the polyethylene glycol ether is 1:0.4-0.6.

[0041] By adopting the above technical solution, when polyethylene glycol and polyethylene glycol ether are used in combination, the polyethylene glycol molecular chain is flexible and relatively linear, and can be filled into the spatial network formed by the polyethylene glycol ether molecular chain and its side chain, and a more compact spatial steric hindrance system is jointly constructed. This synergistic effect can more significantly reduce the interaction force between the slurry particles and the zinc oxide particles, so that the plasticity and flexibility of the target material are enhanced. For example, in the process of pressing the target material, the particles can move and deform more smoothly, reducing the friction and agglomeration between the slurry particles and the zinc oxide particles.

[0042] In the polyethylene glycol and polyethylene glycol ether compound system, polyethylene glycol is first initially adsorbed on the surface of the slurry particles and zinc oxide particles, creating favorable conditions for the further adsorption of polyethylene glycol ether. Polyethylene glycol ether then further enhances the adsorption and dispersion effect on the slurry particles and zinc oxide particles by virtue of its stronger polar interaction and special molecular structure, which makes the slurry particles and zinc oxide particles more evenly dispersed in the plasticizer system, which is beneficial to improving the quality and performance of the target material.

[0043] Since polyethylene glycol and polyethylene glycol ether have similar structures, they have good compatibility. In the mixed system, they are intertwined, reducing the phase separation phenomenon caused by differences in components. This stability is very important during long-term storage or use, which can ensure the uniform distribution of plasticizers in the target material, thereby continuously exerting the plasticizing effect.

[0044] Preferably, the plasticizer comprises polyethylene glycol and polyhydroxyethyl acrylate, and the mass ratio of the polyethylene glycol to the polyhydroxyethyl acrylate is 1:0.2-0.4.

[0045] By adopting the above technical solution, on the one hand, when polyethylene glycol and poly(hydroxyethyl acrylate) are used in combination, the polar interactions of the two complement each other. Polyethylene glycol can be initially adsorbed on the surface of the slurry particles and zinc oxide particles, providing a basis for the further adsorption of poly(hydroxyethyl acrylate), while the strong polar functional groups of poly(hydroxyethyl acrylate) can enhance the adsorption and dispersion effect on the slurry particles and zinc oxide particles. This synergistic effect allows the slurry particles and zinc oxide particles to be better evenly distributed in the plasticizer system, thereby improving the quality and performance of the target material.

[0046] On the other hand, after polyethylene glycol and poly(hydroxyethyl acrylate) are compounded, the flexible molecular chains of polyethylene glycol and the complex spatial structure of poly(hydroxyethyl acrylate) work together. The molecular chains of polyethylene glycol can be filled in the spatial network formed by the molecular chains of poly(hydroxyethyl acrylate), together forming a more compact and complex spatial steric hindrance system. This synergistic effect can more effectively reduce the interaction force between the slurry particles and the zinc oxide particles, and increase the plasticity and flexibility of the target material.

[0047] The presence of polyhydroxyethyl acrylate can also inhibit the rapid decomposition of polyethylene glycol at low temperatures to a certain extent, improve the thermal stability of the system, and reduce the degradation of plasticizers and the decline in performance caused by the increase in temperature during processing, so that the gallium-zirconium co-doped zinc oxide target can maintain good processing performance and plasticization effect in a wider temperature range.

[0048] Preferably, in step S3, the inlet air temperature of the spray drying is 150-250°C, the outlet air temperature is 50-150°C, the spray speed is 8000-15000 rpm, and the sieve mesh size is 40-120 mesh.

[0049] Preferably, in step S4, the hydraulic pressure is 0.04 to 0.07 times the area of ​​the mold (pressure unit is KN, area unit is mm 2 ), the cold pressing pressure is 200~400MPa, and the cold pressing time is 1~100min.

[0050] Preferably, in step S5, the sintering process is divided into a degreasing section, a heating section, a heat preservation section and a cooling section in sequence, and the corresponding sintering temperatures are 0~800℃, 800~1400℃, 1350~1400℃ and cooling to room temperature, respectively, the degreasing rate is 0.01~0.5℃ / min, the heating rate is 0.5~1.0℃ / min, the heat preservation time is 5~20h, the cooling rate is -3℃~-0.5℃ / min, and no gas is passed during sintering.

[0051] Preferably, the preparation method further comprises further processing the obtained gallium-zirconium co-doped zinc oxide target.

[0052] Preferably, the processing steps are specifically as follows: cutting the gallium-zirconium co-doped zinc oxide target into different specifications, adjusting the surface roughness to 0.5-1.0 μm, and then using metal indium for binding, with a binding rate of more than 85%.

[0053] Preferably, the gallium-zirconium co-doped zinc oxide thin film is obtained by magnetron sputtering coating the gallium-zirconium co-doped zinc oxide target prepared by the above preparation method.

[0054] Preferably, the atmosphere used in magnetron sputtering includes O 2 , H 2 , Ar, O in atmosphere2 , H 2 , Ar volume fraction distribution is 2%~5%, 0.1%~0.5%, 93.5%~97.9%; deposition pressure is 0.3~1.5Pa, gas flow rate is 10~25sccm, the distance between target and substrate is 5~10cm, sputtering power is 20~40W, film deposition thickness is 50~400nm, the film is annealed after coating, the annealing temperature is 150℃~400℃, the annealing time is 2~5h, and the temperature is lowered to obtain gallium-zirconium co-doped zinc oxide film.

[0055] In summary, the present application includes at least one of the following beneficial technical effects:

[0056] 1. This application uses gallium and zirconium co-doped zinc oxide targets, based on zirconium (Zr 4+ ) ionic radius, gallium (Ga 3+ ) ionic radius and zinc (Zn 2+ ) have similar ionic radii, Zr 4+ , Ga 3+ Replace Zn 2+ After that, it can provide more electrons and oxygen holes, thereby improving the conductivity and mobility of the film. In addition, after gallium and zirconium are co-doped with zinc oxide, the sintering temperature can be reduced, reducing the damage of the equipment.

[0057] 2. The present application uses the synergistic effect of compound dispersants to form a more stable and uniform dispersion system of metal particles, thereby improving the conductivity and mobility of the film.

[0058] 3. The present application adopts a compound binder and a compound plasticizer, and the synergistic effect between them can more effectively fill the gaps between the particles and optimize the structure of the target material, so that the zinc oxide particles can be tightly sintered together at high temperature, reduce the generation of pores, and increase the relative density; the compound binder bonds the zinc oxide particles into a whole, and the compound plasticizer optimizes the internal conductive properties of the whole, reduces the obstacles to electron transmission, and thus improves the conductivity of the target material. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 is the SEM image of the granular powder in Example 2;

[0060] Figure 2 This is a SEM image of the gallium-zirconium co-doped zinc oxide target after sintering in Example 2;

[0061] Figure 3 This is a picture of the gallium-zirconium co-doped zinc oxide target after processing in Example 2. DETAILED DESCRIPTION

[0062] The present application is further described in detail below with reference to the embodiments.

[0063] In the following embodiments:

[0064] The purity of zirconium oxide, gallium oxide and zinc oxide powders is 99.99%.

[0065] An embodiment of a method for preparing a gallium and zirconium co-doped zinc oxide target material in the present application is as follows:

[0066] Example 1

[0067] This embodiment provides a method for preparing a gallium and zirconium co-doped zinc oxide target, comprising the following steps:

[0068] S1: 10 g zirconium oxide, 25 g gallium oxide, 25.5 g sodium hexadecyl sulfate and 700 g pure water were added into a stirring barrel, stirred and dispersed for 30 min, and then passed into a horizontal sand mill for sand grinding. At a stirring rate of 600 rpm, after sand grinding for 300 min, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 1 with a D90 of 0.65 μm was obtained;

[0069] S2: 4985g zinc oxide, 25.5g sodium hexadecyl sulfate and 1470g pure water were added to another stirring barrel, stirred and dispersed for 30min, then slurry 1 was added, stirred and dispersed for 30min, then 50.2g polyvinyl alcohol and 12.5g polyethylene glycol were added, stirred and dispersed for 180min, and then put into a horizontal sand mill for sand milling. After sand milling for 30min at a stirring rate of 600rpm, the particle size was measured by a Malvern laser particle size analyzer to obtain slurry 2 with a D90 of 0.6μm;

[0070] S3: Transfer the slurry 2 into a spray granulation dryer, set the air inlet temperature to 150°C, the air outlet temperature to 50°C, and the rotation speed to 8000rpm for spray drying and granulation, and then pass through a 40-mesh sieve to obtain a granular powder;

[0071] S4: placing the granular powder in a stainless steel mold of a hydraulic press with a diameter of 160 for preliminary pressing, with the pressure set to 800 KN, and then cold isostatically pressing at a pressure of 200 MPa and holding the pressure for 100 minutes to obtain a green embryo;

[0072] S5: placing the green embryo in a normal pressure furnace for sintering in air atmosphere. The sintering process is divided into a degreasing section of 0-800°C, a heating section of 800-1350°C, a holding section of 1350°C and a cooling section. The holding time is 5 hours. Cooling to room temperature, a gallium-zirconium co-doped zinc oxide target is obtained.

[0073] Among them, the heating rate of the degreasing section is 0.01°C / min, the heating rate of the heating section is 0.5°C / min, and the cooling rate is -3°C / min.

[0074] This embodiment further includes further processing the gallium-zirconium co-doped zinc oxide target obtained in step S5, and the processing steps are as follows:

[0075] The gallium-zirconium co-doped zinc oxide target was placed in a lathe and processed by a wire cutting machine to a size of 70mm×70mm×5mm. It was then polished with 600-mesh and 1000-mesh grinding wheels in turn. The roughness after polishing was 0.5μm. It was then bound with metal indium with a binding rate of 85%, thereby obtaining the processed gallium-zirconium co-doped zinc oxide target (referred to as target).

[0076] Example 2

[0077] This embodiment provides a method for preparing a gallium and zirconium co-doped zinc oxide target, comprising the following steps:

[0078] S1: 75g zirconium oxide, 125g gallium oxide, 30g sodium hexadecyl sulfate and 1500g pure water were added into a stirring barrel, stirred and dispersed for 100min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000rpm, the sand milling was performed for 200min, and the particle size was measured by a Malvern laser particle size analyzer to obtain a slurry 1 with a D90 of 0.5μm.

[0079] S2: Add 4800g zinc oxide, 58g sodium hexadecyl sulfate and 3500g pure water into another stirring barrel, stir and disperse for 100min, then add slurry 1, stir and disperse for 100min, then add 150g polyvinyl alcohol and 50g polyethylene glycol, stir and disperse for 100min, then pass into a horizontal sand mill for sand milling, sand mill for 200min at a stirring rate of 1000rpm, and use a Malvern laser particle size analyzer to measure the particle size to obtain slurry 2 with a D90 of 0.48μm;

[0080] S3: Transfer the slurry 2 into a spray granulation dryer, set the air inlet temperature to 200°C, the air outlet temperature to 80°C, and the rotation speed to 11000 rpm for spray drying and granulation, and then pass through a 60-mesh sieve to obtain a granular powder;

[0081] S4: placing the granular powder in a stainless steel mold of a hydraulic press with a diameter of 160 for preliminary pressing, with the pressure of the hydraulic press set to 1200 KN, and then cold isostatically pressing at a pressure of 300 MPa and holding the pressure for 60 minutes to obtain a green embryo;

[0082] S5: placing the green embryo in a normal pressure furnace for sintering in air atmosphere. The sintering process is divided into a degreasing section of 0-800°C, a heating section of 800-1380°C, a holding section of 1380°C and a cooling section. The holding time is 12 hours. Cooling to room temperature, a gallium-zirconium co-doped zinc oxide target is obtained.

[0083] Among them, the heating rate of the degreasing section is 0.1°C / min, the heating rate of the heating section is 0.8°C / min, and the cooling rate is -2°C / min.

[0084] This embodiment further includes further processing the gallium-zirconium co-doped zinc oxide target obtained in step S5, and the processing steps are as follows:

[0085] The gallium-zirconium co-doped zinc oxide target was placed in a lathe and processed by a wire cutting machine to a size of 70mm×70mm×5mm. It was then polished with 600-mesh and 1000-mesh grinding wheels in turn. The roughness after polishing was 0.75μm. It was then bound with metal indium with a binding rate of 90%, thereby obtaining the processed gallium-zirconium co-doped zinc oxide target (referred to as target).

[0086] Depend on Figure 1 It can be clearly observed that the particles are spherical with uniform size distribution. In the subsequent pressing process, they can not only form a uniform structure but also be more densely packed, which helps to improve the relative density and electrical properties of the target material.

[0087] Depend on Figure 2 It can be clearly observed that the surface of the sintered GaZr co-doped ZnO target presents a relatively uniform state and microscopic roughness, but the grain size and distribution in each area are relatively similar, and there is no obvious abnormal growth or aggregation of local grains. A uniform surface helps to form a stable electron transmission channel, reduce the scattering of electrons during transmission, and reduce resistivity. For the sputtering process, surface uniformity can ensure that the sputtered particles are emitted at a relatively stable rate and angle, which makes the thickness of the film deposited on the substrate uniform and the performance consistent.

[0088] Depend on Figure 3 It can be clearly observed that the surface of the processed GaZr co-doped ZnO target may show a high degree of flatness. The flat surface looks smooth as a mirror in the macroscopic view, without obvious ups and downs or depressions. It can ensure that the sputtered particles are evenly deposited on the substrate to form a high-quality film with uniform thickness.

[0089] Example 3

[0090] This embodiment provides a method for preparing a gallium and zirconium co-doped zinc oxide target, comprising the following steps:

[0091] S1: 150 g zirconium oxide, 250 g gallium oxide, 40 g sodium hexadecyl sulfate and 2500 g pure water were added into a stirring barrel, stirred and dispersed for 180 min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000 rpm, the sand milling was performed for 200 min, and the particle size was measured by a Malvern laser particle size analyzer to obtain a slurry 1 with a D90 of 0.5 μm;

[0092] S2: 4600g zinc oxide, 75g sodium hexadecyl sulfate and 5000g pure water were added to another stirring barrel, stirred and dispersed for 180min, then slurry 1 was added, stirred and dispersed for 180min, then 250g polyvinyl alcohol and 62.5g polyethylene glycol were added, stirred and dispersed for 180min, and then the mixture was passed into a horizontal sand mill for sand milling. After sand milling for 30min at a stirring rate of 2000rpm, the particle size was measured using a Malvern laser particle size analyzer to obtain slurry 2 with a D90 of 0.35μm.

[0093] S3: Transfer the slurry 2 into a spray granulation dryer, set the air inlet temperature to 250°C, the air outlet temperature to 150°C, and the rotation speed to 15000 rpm for spray drying and granulation, and then pass through a 120-mesh sieve to obtain a granular powder;

[0094] S4: placing the granular powder in a stainless steel mold of a hydraulic press with a diameter of 160 for preliminary pressing and forming, with the pressure of the hydraulic press set to 1400 KN, and then cold isostatically pressing at a pressure of 400 MPa and holding the pressure for 1 minute to obtain a green embryo;

[0095] S5: placing the green embryo in a normal pressure furnace for sintering in air atmosphere. The sintering process is divided into a degreasing section of 0-800°C, a heating section of 800-1400°C, a holding section of 1400°C and a cooling section. The holding time is 20 hours. Cooling to room temperature, a gallium-zirconium co-doped zinc oxide target is obtained.

[0096] Among them, the heating rate of the degreasing section is 0.5°C / min, the heating rate of the heating section is 1°C / min, and the cooling rate is -0.5°C / min.

[0097] This embodiment further includes further processing the gallium-zirconium co-doped zinc oxide target obtained in step S5, and the processing steps are as follows:

[0098] The gallium-zirconium co-doped zinc oxide target was placed in a lathe and processed by a wire cutting machine to a size of 70mm×70mm×5mm. It was then polished with 600-mesh and 1000-mesh grinding wheels in turn. The roughness after polishing was 1μm. It was then bound with metal indium with a binding rate of 95%, thereby obtaining the processed gallium-zirconium co-doped zinc oxide target (referred to as target).

[0099] Example 4

[0100] The difference between this embodiment and embodiment 2 is that:

[0101] S1: 75g zirconium oxide, 125g gallium oxide, 15g sodium hexadecyl sulfate, 15g sodium polyacrylate and 1500g pure water were added into a stirring barrel, stirred and dispersed for 180min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000rpm, after sand grinding for 200min, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 1 with a D90 of 0.5μm was obtained;

[0102] S2: 4800g zinc oxide, 29g sodium hexadecyl sulfate, 29g sodium polyacrylate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, then 150g polyvinyl alcohol and 50g polyethylene glycol were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 2 with a D90 of 0.48μm was obtained;

[0103] The rest is the same as in Example 2.

[0104] Example 5

[0105] The difference between this embodiment and embodiment 2 is that:

[0106] S2: 4800g zinc oxide, 29g sodium hexadecyl sulfate, 29g sodium polyacrylate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, then 81.8g polyvinyl alcohol, 68.2g hydroxypropyl methylcellulose, 35.7g polyethylene glycol and 14.3g polyethylene glycol ether were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used for particle size detection to obtain slurry 2 with a D90 of 0.48μm;

[0107] The rest is the same as in Example 2.

[0108] Example 6

[0109] The difference between this embodiment and embodiment 5 is that:

[0110] S1: 75g zirconium oxide, 125g gallium oxide, 7.5g sodium hexadecyl sulfate, 22.5g sodium polyacrylate and 1500g pure water were added into a stirring barrel, stirred and dispersed for 180min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000rpm, after sand grinding for 200min, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 1 with a D90 of 0.5μm was obtained;

[0111] S2: 4800g zinc oxide, 14.5g sodium hexadecyl sulfate, 43.5g sodium polyacrylate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, then 87.5g polyvinyl alcohol, 62.5g hydroxypropyl methylcellulose, 31.3g polyethylene glycol and 18.7g polyethylene glycol ether were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used for particle size detection to obtain slurry 2 with a D90 of 0.48μm;

[0112] The rest is the same as Example 5.

[0113] Example 7

[0114] The difference between this embodiment and embodiment 6 is that:

[0115] S1: 75g zirconium oxide, 125g gallium oxide, 10g sodium hexadecyl sulfate, 20g sodium polyacrylate and 1500g pure water were added into a stirring barrel, stirred and dispersed for 180min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000rpm, after sand grinding for 200min, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 1 with a D90 of 0.5μm was obtained;

[0116] S2: 4800g zinc oxide, 19.3g sodium hexadecyl sulfate, 38.7g sodium polyacrylate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, then 84.5g polyvinyl alcohol, 65.2g hydroxypropyl methylcellulose, 33.3g polyethylene glycol and 16.7g polyethylene glycol ether were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used for particle size detection to obtain slurry 2 with a D90 of 0.48μm;

[0117] The rest is the same as Example 6.

[0118] Example 8

[0119] The difference between this embodiment and embodiment 7 is that:

[0120] S1: 75 g zirconium oxide, 125 g gallium oxide, 6.9 g sodium hexadecyl sulfate, 23.1 g sodium hexametaphosphate and 1500 g pure water were added into a stirring barrel, stirred and dispersed for 180 min, and then passed into a horizontal sand mill for sand milling. At a stirring rate of 1000 rpm, sand milling was performed for 200 min, and particle size was measured using a Malvern laser particle size analyzer to obtain slurry 1 with a D90 of 0.5 μm.

[0121] S2: 4800g zinc oxide, 13.4g sodium hexadecyl sulfate, 44.6g sodium hexametaphosphate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, then 50g polyacrylic acid, 100g polyvinyl alcohol, 41.7g polyethylene glycol and 8.3g polyhydroxyethyl acrylate were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used for particle size detection to obtain slurry 2 with a D90 of 0.48μm;

[0122] The rest is the same as Example 7.

[0123] Example 9

[0124] The difference between this embodiment and embodiment 8 is that:

[0125] S1: 75g zirconium oxide, 125g gallium oxide, 12.4g sodium hexadecyl sulfate, 17.6g sodium hexametaphosphate and 1500g pure water were added into a stirring barrel, stirred and dispersed for 180min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000rpm, after sand grinding for 200min, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 1 with a D90 of 0.5μm was obtained;

[0126] S2: 4800g zinc oxide, 23.9g sodium hexadecyl sulfate, 34.1g sodium hexametaphosphate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, and then 61.8g polyacrylic acid, 88.2g polyvinyl alcohol, 35.7g polyethylene glycol and 14.3g polyhydroxyethyl acrylate were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used for particle size detection to obtain slurry 2 with a D90 of 0.48μm;

[0127] The rest is the same as Example 8.

[0128] Example 10

[0129] The difference between this embodiment and embodiment 9 is that:

[0130] S1: 75g zirconium oxide, 125g gallium oxide, 10g sodium hexadecyl sulfonate, 20g sodium hexametaphosphate and 1500g pure water were added into a stirring barrel, stirred and dispersed for 180min, and then passed into a horizontal sand mill for sand grinding. At a stirring rate of 1000rpm, after sand grinding for 200min, a Malvern laser particle size analyzer was used to measure the particle size, and a slurry 1 with a D90 of 0.5μm was obtained;

[0131] S2: 4800g zinc oxide, 19.3g sodium hexadecyl sulfate, 38.7g sodium hexametaphosphate and 3500g pure water were added to another stirring barrel, stirred and dispersed for 100min, then slurry 1 was added, stirred and dispersed for 100min, then 56.2g polyacrylic acid, 93.8g polyvinyl alcohol, 38.5g polyethylene glycol and 11.5g polyhydroxyethyl acrylate were added, stirred and dispersed for 100min, and then passed into a horizontal sand mill for sand milling. After sand milling for 200min at a stirring rate of 1000rpm, a Malvern laser particle size analyzer was used for particle size detection to obtain slurry 2 with a D90 of 0.48μm;

[0132] The rest is the same as Example 9.

[0133] Comparative Example 1

[0134] The difference between this comparative example and Example 2 is:

[0135] S1: 200 g of gallium oxide, 30 g of sodium hexadecyl sulfate and 1500 g of pure water were added to a stirring barrel, stirred and dispersed for 100 min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000 rpm, the sand milling was performed for 200 min, and the particle size was measured using a Malvern laser particle size analyzer to obtain a slurry 1 with a D90 of 0.5 μm;

[0136] The rest is the same as in Example 2.

[0137] Comparative Example 2

[0138] The difference between this comparative example and Example 2 is:

[0139] S1: 200 g of aluminum oxide, 30 g of sodium hexadecyl sulfate and 1500 g of pure water were added to a stirring barrel, stirred and dispersed for 100 min, and then put into a horizontal sand mill for sand grinding. At a stirring rate of 1000 rpm, the sand milling was performed for 200 min, and the particle size was measured using a Malvern laser particle size analyzer to obtain a slurry 1 with a D90 of 0.5 μm;

[0140] The rest is the same as in Example 2.

[0141] Performance Testing

[0142] (1) Physical properties test of target material

[0143] The relative density of the target materials in Examples 1 to 10 and Comparative Examples 1 to 2 was tested by the Archimedean drainage method; the resistivity of the target materials in Examples 1 to 10 and Comparative Examples 1 to 2 was tested by a four-point resistivity meter. The test results are shown in Table 1.

[0144] (2) Electrical properties test of GaZr co-doped ZnO thin film (referred to as thin film)

[0145] A magnetron sputtering device was used to sputter thin films with a thickness of 50 to 400 nm on quartz glass using the target materials in Examples 1 to 10 and Comparative Examples 1 to 2 as raw materials, respectively. The resistivity of the thin films was tested using a four-point resistivity meter, and the mobility of the thin films was tested using a Hall effect tester. The test results are shown in Table 1.

[0146] ① The target material in Example 1 is installed at the corresponding position of the magnetron target gun, and magnetron sputtering coating is performed, and quartz glass is used as the substrate, and the substrate temperature is maintained at 400°C. After coating, it is placed in an annealing furnace, the temperature is set to 150°C, the annealing time is 5h, and then cooled with the furnace to obtain a thin film;

[0147] The magnetron sputtering coating process parameters are: the sputtering deposition pressure is 0.3Pa, the sputtering power is 20W, and the sputtering atmosphere is O 2 , H 2 , Ar, O in atmosphere 2 , H 2 , Ar volume fraction is: 2%, 0.1%, 97.9%, the gas flow rate is 10sccm, the distance from the target to the substrate is 5cm, and the film deposition thickness is 50nm.

[0148] ② The targets in Example 2, Examples 4 to 10 and Comparative Examples 1 to 2 were respectively installed at the corresponding positions of the magnetron target gun, and magnetron sputtering coating was performed, and quartz glass was used as the substrate, and the substrate temperature was maintained at 400° C. After coating, it was placed in an annealing furnace, the temperature was set to 250° C., the annealing time was 3.5 h, and then cooled with the furnace to obtain a thin film;

[0149] The magnetron sputtering coating process parameters are: the sputtering deposition pressure is 0.3Pa, the sputtering power is 30W, and the sputtering atmosphere is O 2 , H 2 , Ar, O in atmosphere 2 , H 2 , Ar volume fraction is: 3.5%, 0.25%, 96.25%, the gas flow rate is 18 sccm, the distance from the target to the substrate is 7 cm, and the film deposition thickness is 200 nm.

[0150] ③ The target material in Example 3 was installed at the corresponding position of the magnetron target gun, and magnetron sputtering coating was performed, and quartz glass was used as the substrate, and the substrate temperature was maintained at 400°C. After coating, it was placed in an annealing furnace, the temperature was set to 400°C, the annealing time was 5h, and then cooled with the furnace to obtain a thin film;

[0151] The magnetron sputtering coating process parameters are: the sputtering deposition pressure is 0.3Pa, the sputtering power is 40W, and the sputtering atmosphere is O 2 , H 2 , Ar, O in atmosphere 2 , H 2 , Ar volume fraction is: 5%, 0.5%, 94.5%, the gas flow rate is 25sccm, the distance from the target to the substrate is 10cm, and the film deposition thickness is 400nm.

[0152] Table 1 Physical properties of the targets in Examples 1 to 10 and Comparative Examples 1 to 2 and electrical properties of the corresponding target sputtered films

[0153]

[0154] By comparing and analyzing Examples 1 to 3, it can be seen that by optimizing and adjusting the doping amount of gallium oxide and zirconium oxide, when the mass of gallium oxide accounts for 2.5% of the total mass of the metal oxide, and when the mass of zirconium oxide accounts for 1.5% of the total mass of the metal oxide, the target material obtained has a higher relative density and a lower resistivity. When the target material obtained in Examples 1 to 3 is further magnetron sputtered, the film sputtered by the target material obtained in Example 2 has a lower resistivity and a higher mobility. This is because an appropriate amount of gallium oxide and zirconium oxide doped into zinc oxide will provide additional electrons as carriers, increase the conductivity of the target material, and thus reduce the resistivity of the target material. However, if the doping amount is too much, it may destroy the crystal structure of zinc oxide and lead to enhanced impurity scattering, which in turn increases the resistivity.

[0155] By comparing and analyzing Example 2 and Comparative Examples 1-2, it can be seen that the relative density of the target material is improved and the resistivity is lower by using gallium oxide and zirconium oxide for compound doping. This is because: first, zirconium oxide has a higher melting point and hardness, which can promote the sintering of zinc oxide and gallium oxide, reduce the formation of pores, and increase the relative density of the target material. The higher relative density can make the sputtering process more stable and improve the electrical properties of the film.

[0156] Secondly, when gallium oxide and zirconium oxide are compound-doped, it helps to form a solid solution and may improve the migration environment of carriers. The presence of zirconium oxide may also adjust the electric field distribution inside the lattice, reduce the number of carrier scattering centers, and improve the electrical properties of the sputtered film.

[0157] Finally, the radius of zirconium ions in zirconium oxide, the radius of gallium ions in gallium oxide and the radius of zinc ions in zinc oxide are relatively close. The presence of the two doping ions may provide more opportunities for interaction and adaptation with the lattice, and may be easier to enter the interstitial positions of the main lattice or replace the main ions without causing excessive lattice distortion, which is conducive to the formation of solid solution, making the structure of the target material denser and the relative density increased.

[0158] By comparing and analyzing Example 2 and Examples 3 to 10, it can be seen that, firstly, after the composite dispersant of sodium polyacrylate and sodium hexadecyl sulfate is used, a synergistic dispersion effect is achieved. In the preparation of zinc oxide target material, the uniformly dispersed metal oxide particles can be more densely stacked, increasing the contact area between the particles and reducing the pores between the particles, thereby increasing the relative density of the target material and reducing the resistivity of the target material.

[0159] Secondly, after sodium hexametaphosphate is compounded with sodium hexadecyl sulfonate, sodium hexametaphosphate has a strong complexing ability for metal ions. After compounding with sodium hexadecyl sulfonate, it can be better adsorbed on the surface of the target particles, and through complexation and its own steric hindrance effect, it prevents the mutual aggregation of particles, making the target particles more evenly dispersed in the system. This uniform dispersion state helps to reduce the contact resistance between particles, thereby reducing the resistivity of the target material. In addition, the evenly dispersed particles can better fill the pores during the molding process and increase the relative density of the target material.

[0160] Finally, polyvinyl alcohol and hydroxypropyl methylcellulose are used as a binder, and polyethylene glycol and polyethylene glycol ether are used as a plasticizer. The strong hydrogen bonding effect of polyvinyl alcohol and the flexibility of the hydroxypropyl methylcellulose molecular chain cooperate with each other, so that the binder can better fit on the surface of the target particles. This complementary bonding mechanism can make the bonding between particles more firm, reduce the migration of particles during processing, and thus help to improve the relative density of the target. At the same time, because the bonding between the target particles is more firm, a continuous bonding phase can be better formed during the sintering process. This bonding phase can fill the gaps between the particles and maintain a certain stability at high temperatures, making the target structure more compact. The dense structure is conducive to the conduction of electrons, because the electrons encounter fewer obstacles when transmitting in it, thereby reducing the resistivity of the target.

[0161] After polyethylene glycol and polyethylene glycol ether are compounded, on the one hand, they can better penetrate between the molecular chains of the binder, reduce the interaction force between the molecular chains, and make the binder softer and easier to flow. This property helps the binder to better fill the gaps between particles when pressing the target material, thereby increasing the relative density of the target material. On the other hand, more continuous and unobstructed channels can be formed inside the target material. These channels help the transmission of electrons and reduce the resistance encountered by electrons during the transmission process. At the same time, the plasticizer can reduce the insulation of the binder, making it easier for electrons to move around the binder phase, thereby reducing the resistivity of the target material.

[0162] Compared with the use of polyvinyl alcohol and polyacrylic acid compound binder, polyethylene glycol and polyhydroxyethyl acrylate compound plasticizer, and polyvinyl alcohol and hydroxypropyl methylcellulose compound binder, polyethylene glycol, and polyethylene glycol ether compound plasticizer, the relative density of the target material can be further improved and the resistivity can be reduced. This is because polyacrylic acid has carboxyl groups, which can form coordination bonds with metal ions on the surface of the particles, and can also interact with other components through hydrogen bonds. The coexistence of hydrogen bonds and coordination bonds makes the bonding force between the binder and the target particles stronger, forming a closer connection between the particles. After polyacrylic acid and polyvinyl alcohol are compounded, they can form a thinner and more uniform bonding layer on the surface of the particles. This bonding layer can make the contact between the particles closer, which is conducive to the close stacking of the particles during the pressing and sintering process, thereby increasing the relative density of the target material.

[0163] During the sintering process, the composite binder of polyvinyl alcohol and polyacrylic acid can undergo a partial cross-linking reaction at a relatively low temperature. This cross-linking reaction can enhance the cohesive force of the binder, so that the binder can still maintain its bonding effect on the particles at high temperatures, and prevent the particles from reaggregating or shifting due to heat during the sintering process. At the same time, the cross-linked binder can better fill the gaps between the particles, making the target structure more compact, reducing the porosity, and increasing the relative density. Moreover, the dense structure is conducive to electron transmission, reducing electron scattering, and thus reducing resistivity.

[0164] Compared with polyethylene glycol and polyethylene glycol ether compound plasticizers, polyethylene glycol and poly(hydroxyethyl acrylate) compound plasticizers may have more advantages in adjusting the fluidity of the binder. This is because poly(hydroxyethyl acrylate) can form a more specific interaction with the binder, allowing the plasticity of the binder to be more accurately adjusted, which helps to obtain a denser target structure during the molding process.

[0165] In addition, polyethylene glycol and compound plasticizer can form more continuous conductive channels inside the target material. The hydroxyl and ester groups in polyhydroxyethyl acrylate can interact with some components in the target material to adjust the local electrical environment. At the same time, the good fluidity of polyethylene glycol helps to keep these channels unobstructed, allowing electrons to be transmitted more smoothly in the target material, further reducing the resistivity.

Claims

1. A method for preparing a gallium and zirconium co-doped zinc oxide target, characterized in that: The steps include: S1: mixing zirconium oxide, gallium oxide, water and a dispersant uniformly, grinding and obtaining slurry 1; S2: After zinc oxide, water and dispersant are mixed evenly, slurry 1 is added, mixed evenly, and then a binder and a plasticizer are added, mixed evenly, and ground to obtain slurry 2; S3: spray-drying and granulating the slurry 2, and sieving to obtain granular powder; S4: hydraulically and cold isostatically press the granular powder to obtain a green embryo; S5: sintering the green embryo, and after cooling, obtaining a gallium-zirconium co-doped zinc oxide target; The dispersant is sodium hexadecyl sulfonate and sodium polyacrylate, or the dispersant is sodium hexametaphosphate and sodium hexadecyl sulfonate; The plasticizer is polyethylene glycol and polyethylene glycol ether, or the plasticizer includes polyethylene glycol and polyhydroxyethyl acrylate; The zirconium oxide accounts for 1.5% to 3% of the total mass of the metal oxide, and the gallium oxide accounts for 2.5% to 5% of the total mass of the metal oxide.

2. The method for preparing a gallium and zirconium co-doped zinc oxide target according to claim 1, characterized in that: In step S1, the dispersant accounts for 0.5% to 0.8% of the total mass of the metal oxide, and water accounts for 15% to 50% of the total mass of the metal oxide.

3. The method for preparing a gallium and zirconium co-doped zinc oxide target according to claim 2, characterized in that: In step S2, zinc oxide accounts for 92% to 99.3% of the total mass of the metal oxide, water accounts for 30% to 100% of the total mass of the metal oxide, the dispersant accounts for 0.5% to 1.5% of the total mass of the metal oxide, the binder accounts for 1% to 5% of the total mass of the metal oxide, and the plasticizer accounts for 0.25% to 1.25% of the total mass of the metal oxide.

4. The method for preparing a gallium and zirconium co-doped zinc oxide target according to claim 3, characterized in that: The binder is polyvinyl alcohol and hydroxypropyl methylcellulose, or polyacrylic acid and polyvinyl alcohol.

5. The method for preparing a gallium and zirconium co-doped zinc oxide target according to claim 4, characterized in that: In step S5, the sintering temperature is divided into a degreasing section, a heating section, a heat preservation section, and a cooling section in sequence, and the corresponding sintering temperatures are 0~800℃, 800~1400℃, 1350~1400℃ and cooling to room temperature, respectively. The degreasing rate is 0.01~0.5℃ / min, the heating rate is 0.5~1.0℃ / min, the heat preservation time is 5~20h, the cooling rate is 0.5℃~3℃ / min, and no gas is passed during the sintering process.

Citation Information

Patent Citations

  • Gallium oxide-zinc oxide sputtering target, method for forming transparent conductive film, and transparent conductive film

    CN101208452A

  • Zinc oxide-based sputtering target, method of fabricating thereof and thin film transistor

    CN103510056A